2016
DOI: 10.1103/physrevb.93.014421
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic dipole interactions in crystals

Abstract: The influence of magnetic dipole interactions (MDIs) on the magnetic properties of local-moment Heisenberg spin systems is investigated. A general formulation is presented for calculating the eigenvalues λ and eigenvectorsμ of the MDI tensor of the magnetic dipoles in a line (one dimension 1D), within a circle (2D) or sphere (3D) of radius r surrounding a given moment µi for given magnetic propagation vectors k for collinear and coplanar noncollinear magnetic structures on both Bravais and non-Bravais spin lat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
62
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 61 publications
13
62
2
Order By: Relevance
“…3 up to H = 800 Oe for all three compositions is χ c ≡ dM c /dH ≈ 0.077. This value is about the same as the value χ c = 1/4π ≈ 0.080 expected if M c /H in the absence of demagnetization effects is so large that the observed value is limited by the demagnetization factor [35]. Hence the magnetic response along the c axis is extremely soft for x = 0.19, 0.25 and 0.28, which may be expected if these compositions are in a crossover region in the magnetocrystalline anisotropy field from being parallel to perpendicular to the c axis.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…3 up to H = 800 Oe for all three compositions is χ c ≡ dM c /dH ≈ 0.077. This value is about the same as the value χ c = 1/4π ≈ 0.080 expected if M c /H in the absence of demagnetization effects is so large that the observed value is limited by the demagnetization factor [35]. Hence the magnetic response along the c axis is extremely soft for x = 0.19, 0.25 and 0.28, which may be expected if these compositions are in a crossover region in the magnetocrystalline anisotropy field from being parallel to perpendicular to the c axis.…”
supporting
confidence: 68%
“…Finally, for x = 0.52, a PM behavior is observed. As a point of reference, the magnetic dipole interaction between local moments on a simple-tetragonal lattice with c/a ≈ 3.65 as in CaCo 2−y As 2 predicts that the ordered moments should lie in the ab plane [35].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13(a). The T dependence of the anisotropy is too strong to arise from the conventional shape-, magneticdipole and single-ion anisotropies [68]. It may arise from c-axis FM correlations that grow with decreasing T faster than predicted by MFT and/or from interactions between the Eu and Mn spin sublattices.…”
Section: A Magnetization and Magnetic Susceptibilitymentioning
confidence: 89%
“…[16] In fact, the application of spin models in the study of dielectric and magnetic properties of materials has a long history. [17][18][19][20][21][22][23][24][25][26][27][28][29] One particularly interesting result, found by Luttinger and Tisza, [19] is that the ground state of a simple cubic lattice of dipoles in the absence of an external field is two-site periodic along all three lattice axes and has no net polarization. Belobrov et al [23] later showed that in three dimensions such a lattice has an infinitely degenerate ground state, as we shall explain in more detail below.…”
mentioning
confidence: 99%